2017
DOI: 10.1007/s40641-017-0056-z
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Deposition Impacts on Land and Ocean Carbon Cycles

Abstract: Purpose of Review Atmospheric aerosol deposition is an important source of nutrients and pollution to many continental and marine ecosystems. Humans have heavily perturbed the cycles of several important aerosol species, potentially affecting terrestrial and marine carbon budgets and consequently climate. The most ecologically important aerosol elements impacted by humans are nitrogen, sulfur, iron, phosphorus, and base cations. Here, we review the latest research on the modification of the atmospheric cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
101
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 200 publications
0
101
0
1
Order By: Relevance
“…Mahowald et al (2017) indicated that during dust events, AOD can be used as a reliable tool to represent dust loading in the atmosphere. High AOD values were observed in Mongolia, Inner Mongolia, Hexi Corridor, the eastern Taklimakan Desert, and the Northwest China Plain (Fig.…”
Section: Trajectory Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Mahowald et al (2017) indicated that during dust events, AOD can be used as a reliable tool to represent dust loading in the atmosphere. High AOD values were observed in Mongolia, Inner Mongolia, Hexi Corridor, the eastern Taklimakan Desert, and the Northwest China Plain (Fig.…”
Section: Trajectory Modelmentioning
confidence: 99%
“…We estimated that 0.9 Tg of dust was deposited over North America. Iron deposition over the North Pacific Ocean was estimated by ourselves to be 0.19 Tg, assuming the dust contained 3.5 % iron (Luo et al, 2005;Mahowald et al, 2017). Transport of dust emitted from East Asian desert sources is highly dependent on atmospheric circulation (Zhang et al, 1997).…”
Section: Atmospheric Dust Depositionmentioning
confidence: 99%
See 3 more Smart Citations